Regulating Algorithmic Management at Work in the European Union: Data Protection, Non-Discrimination and Collective Rights - Aloisi, Antonio (International Journal of Comparative Labour Law and Industrial Relations, 2024)
In recent years, algorithmic management practices have been widely adopted by employers to monitor remote work, analyse how applicants behave during job interviews, rate workers' performance and calculate wage adjustments. As a consequence, the condition of workers being subjected to the upstream authority of managers has intensified. Employment protection legislation recognises the importance of curbing the bosses' unilateral discretionary power by deploying several controlling factors. However, the traditional guardrails have now been displaced by the transformative impetus of data-driven technologies. As a response to this challenge, several European Union law tools could be pragmatically adapted to curtail the expansion of managers' decisional leeway. By applying a multidimensional, anticipatory and participatory approach, this paper integrates substantive and procedural rules that contribute to rebalancing informational asymmetries within workplaces and assesses the effectiveness of those rules. Using examples from case law, administrative decisions and legislative developments, it also discusses the mutually reinforcing relationship between data protection provisions and anti-discrimination measures, which renders automated decisions documentable and contestable. Beyond defensive tactics, this paper calls for the involvement of worker representatives in co-designing digital human resources policies. Indeed, as data are relational, collective bodies are uniquely placed to exchange information, raise awareness and bring claims, thereby preventing algorithmic abuses.
Keywords: Employer powers;Data protection;Non-discrimination;Codetermination;Artificial intelligence;Algorithms' management;Right to explanation;Burden of proof;EU law;Digital transformation; Employer powers; Data protection; Non-discrimination; Codetermination; Artificial intelligence; Algorithms' management; Right to explanation; Burden of proof; EU law; Digital transformation